METALLOGENY OF UKRAINE TITANIUM - Galeckiy, L.; Remezova, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The ore-concentration factors and conditions of titanium deposits of a different genesis are considered in the article. The conformities to the natural law of genetic row of deposits forming from primary to placer are exposed. A typification of deposits connected with layered titanium-bearing intrusions of gabbro is conducted and the prospects of their development are outlined